2009
DOI: 10.1158/1078-0432.ccr-08-2347
|View full text |Cite
|
Sign up to set email alerts
|

Extranuclear Coactivator Signaling Confers Insensitivity to Tamoxifen

Abstract: Purpose: Tamoxifen is one of many standard therapeutic options currently available for estrogen receptor-α-positive breast cancer patients. Emerging data have suggested that levels of estrogen receptor coregulatory proteins play a significant role in acquiring resistance to antiestrogen action. It has been suggested that high levels of estrogen receptor coactivators and its mislocalization may enhance the estrogen agonist activity of tamoxifen and contribute to tamoxifen resistance. Experimental Design: In an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 29 publications
2
64
0
Order By: Relevance
“…This pathway confers tamoxifen resistance for breast cancer cells through the activation of both the PI3K/Akt and Src/MAPK pathways [62]. PELP1-transgenic mice, which express cytoplasmic PELP1 in mammary gland tumors, display tamoxifen resistance, suggesting that these extranu-clear actions are responsible for the drug resistance [76]. PELP1 has also been implicated in aromatase regulation in breast cancer cells through a short extranuclear auto-crine loop between E2 and aromatase expression [77].…”
Section: E2 Signaling In Breast Carcinogenesismentioning
confidence: 99%
“…This pathway confers tamoxifen resistance for breast cancer cells through the activation of both the PI3K/Akt and Src/MAPK pathways [62]. PELP1-transgenic mice, which express cytoplasmic PELP1 in mammary gland tumors, display tamoxifen resistance, suggesting that these extranu-clear actions are responsible for the drug resistance [76]. PELP1 has also been implicated in aromatase regulation in breast cancer cells through a short extranuclear auto-crine loop between E2 and aromatase expression [77].…”
Section: E2 Signaling In Breast Carcinogenesismentioning
confidence: 99%
“…In breast cancer studies, PELP1 is restricted to the nucleus of normal MEC but is partially to largely cytoplasmic in a significant number of breast tumors in which its altered localization is associated with tamoxifen resistance (Vadlamudi et al 2005, Kumar et al 2009). Mechanistic studies conducted in cancer cell lines demonstrated that altered localization of PELP1 to the cytoplasm augments intracellular c-Src, MAPK, and AKT signaling (Fig.…”
Section: Pr Signaling Cross Talk Is Relevant To Er+ Luminal Breast Camentioning
confidence: 99%
“…Several studies have indicated that the deregulation of PELP1 contributes to therapy resistance and that the knockdown of PELP1 or blockage of PELP1-mediated extranuclear signaling sensitizes cells to therapy , Nagpal et al 2008, Kumar et al 2009. Interestingly, the subcellular localization of PELP1 is dysregulated in tumors with a cytosolic predominance in a subset of endometrial tumors, which exhibit resistance to tamoxifen anti-hormonal therapy.…”
Section: Pelp1 and Therapy Resistancementioning
confidence: 99%
“…Interestingly, the subcellular localization of PELP1 is dysregulated in tumors with a cytosolic predominance in a subset of endometrial tumors, which exhibit resistance to tamoxifen anti-hormonal therapy. Patients whose tumors have high levels of cytoplasmic PELP1 respond poorly to tamoxifen therapy compared with patients whose tumors have low levels of cytoplasmic PELP1 (Kumar et al 2009). These observations are in agreement with results from an experiment in which tamoxifen-susceptible MCF-7 cells engineered to express PELP1 in cytosol (by modification the nuclear localization sequence) were found to exhibit resistance to tamoxifen , Kumar et al 2009, Gonugunta VK, Sareddy GR, Krishnan SR, Cortez V, Roy SS, Tekmal RR & Vadlamudi RK, 2014.…”
Section: Pelp1 and Therapy Resistancementioning
confidence: 99%